INTERNATIONAL ECONOMIC INTEGRATION PROCESSES AND THE ROLE OF REGIONAL ORGANIZATIONS - Khakimdjonov Bekhruz Khasan ugli, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract. International economic integration has become a defining trend of the global economy in the twenty-first century. By reducing trade barriers, harmonizing policies, and strengthening cooperation, integration promotes economic growth, stability, and competitiveness. Regional organizations such as the European Union (EU), the Association of Southeast Asian Nations (ASEAN), the African Union (AU), and the Eurasian Economic Union (EAEU) play pivotal roles in advancing these processes. This article analyzes the nature of economic integration, its stages, benefits, and challenges, while emphasizing the contribution of regional organizations to global economic governance and sustainable development.